Produk alat ukur tinggi dan berat badan pendeteksi stunting dengan fitur hiburan untuk anak usia 2-5 tahun - Michele Ludya; Yanuar Herlambang; Dandi Yunidar (Institut Seni Indonesia Yogyakarta, 2023)
The process of measuring the height and weight of toddlers regularly is very important to be carried out to prevent and handle stunting from an early age. These measurements are often carried out using separate height and weight measuring instruments, and there are still many Posyandu in Indonesia that use conventional instruments that are less safe, less accurate, and less comfortable, which results in discomfort and difficulties in the measurement process, both for Posyandu cadres, as well as the children themselves. In addition, there are still not many stunting detection tools made according to the characteristics of toddlers. Therefore, this study was conducted to find systems, types of height and weight measuring instruments that are practical and accurate, with visualization, product ergonomics, and features that are by the characteristics of toddlers, so that the measurement process can be more accurate, comfortable, safe, and pleasant with design thinking methods and ergonomic approaches. The result of this design is the design of an Arduino-based digital stunting detection tool in the form of a fox and equipped with a phone holder plus a plush-toys feature to attract children's attention which could be used to measure a child's weight and height simultaneously, as well as placing a device